Investigation of Human Errors in Emergency Department of Imam Khomeini Hospital Emergency Department of Jiroft Using Systematic Human Error Reduction and Prediction Approach - Reza JAFARI NODOUSHAN; Khalil TAHERZADEH-CHENANI; Mehdi NAKHAEE-NEZHAD; Sepideh SHAHSAVARI (Shahid Sadoughi University of Medical Sciences, 2021)
Introduction: In examining the unfortunate events that have taken place in the industrial and health sectors, human error is considered as the main cause of these events. Given the sensitivity and importance of medical careers, the occurrence of errors can lead to irreparable consequences. The purpose of this study was to investigate the human error in the emergency department of Imam Khomeini Hospital in Jiroft. methods: This study was a cross-sectional and descriptive one. Emergency nurses' job duties have been analyzed by interviewing emergency nurses and studying nursing job guidelines and procedures using hierarchical task analysis. Finally, using the Systematic Human Error Reduction and Prediction Approach, human errors in nursing care were analyzed. Results: Generally, 4 tasks, 18 sub-tasks and 91 types of errors related to nursing activities were identified. Number of errors found, 27 (30%) Action errors, 18 (20%) Checking errors, 19 (21%) Retrieval errors, 12 (13%) communication errors, and 15 (16%) selection errors Were. As can be seen, the largest number of errors was related to the type of Action errors. Conclusion: Considering the results of the present study, the highest numbers of errors were related to Action and Checking errors respectively, which due to the sensitivity of nursing jobs and especially in the emergency department, require the use of highly skilled people to perform tasks that require high concentration and accuracy.